Peanut butter panic - Flower, Amanda (Flower, Amanda. Amish candy shop mystery, 2022)
"Thanksgiving is Bailey King's busiest holiday weekend. This year promises to be even more hectic, since Bailey's candy shop, Swissmen Sweets, is providing desserts for Harvest, Ohio's first village-wide Thanksgiving celebration. Yet, even with a guest list close to seven hundred people--Amish and English alike--the event's organizer, Margot Rawlings, is unfazed ... until she discovers her mother, former judge Zara Bevan, will be in attendance. Zara's reputation as a harsh critic is matched only by her infamy as a judge who has actively harmed the Amish community. So no one is prepared when Zara arrives with much younger boyfriend Blaze Smith and reveals their impending nuptials at dinner. That should have been the day's biggest news, except shortly after the announcement, Blaze suffers an allergic reaction to something he's eaten and dies on the spot. Now, Bailey's desserts are prime suspects, along with Margot and nearly everyone who attended the meal. With such a cornucopia of possibilities, Bailey must dig in and get to the bottom of this murder, before the killer goes up for seconds ..."--